Assessing the impact of mHealth on the autonomy of diabetic patients: a systematic review - Pincus, Shannon (Department of Human Biology, 2026)
Background mHealth has emerged as a major modality for the provision of healthcare and it is generally proposed that mHealth interventions improve patient autonomy. Diabetes mellitus requires chronic management to mitigate a myriad of serious complications. mHealth uses features such as regular reminders to encourage patient engagement with health treatments. This may assist with chronic diabetes management. This systematic review aims to answer the research question: What is the impact of mHealth interventions on patient autonomy? Methods A systematic review was conducted, in accordance with the PRISMA-P 2020 checklist, to critically assess the literature from the following databases: PubMed, Scopus, Cochrane Library, Web of Science, EBSCO, Africawide, Academic Search Premier, CINAHL and APA PsycInfo. Both free text words and medical subject heading terms [MeSH] were used as required. Both randomised and nonrandomised studies were reviewed, and studies were considered eligible if they met the predetermined inclusion criteria as follows: populations over 18 years of age and diagnosed with diabetes mellitus type 1, diabetes mellitus type 2 or gestational diabetes, using an mHealth intervention where the outcome related to patient autonomy. A thematic analysis was conducted to critically assess the articles. Results Eighteen studies that met the eligibility criteria were included in this systematic review. 12 of the articles focused on patients with diabetes mellitus type 2, 3 focused on both types 1 and 2, 1 focused on gestational diabetes and 2 articles were unclear on the type of diabetes considered. The interventions used included interactive voice response interventions, text messages, phone calls and mHealth applications. Outcomes primarily focused on health literacy and various health outcomes such as medication adherence, healthy eating, exercise, and glycated haemoglobin (HbA1c). The thematic analysis revealed that there were challenges with conceptualising autonomy and mHealth, rather focusing on what seem to be components of autonomy, such as self-management. Despite this, the articles seem to suggest mHealth may have some value in improving patient autonomy. Discussion In critically assessing the literature it seemsthat mHealth does promote the components of autonomy of diabetic patients, especially through text-messaging based interventions that act as reminders and support patients. However, this is tempered by the issues surrounding the concept of autonomy. There is a lack of critical thought and interrogation around autonomy. The articles do not define autonomy or measure autonomy, rather focussing on the components of autonomy such as selfmanagement, health literacy and improved health outcomes. The complexities surrounding the concept of autonomy, such as the focus on rationality, diminish its utility in a healthcare setting. Instead, it is the components of autonomy that offer a better tool for driving behaviour change in diabetic patients. Conclusion mHealth may improve the components of autonomy (such as self-management, health literacy and improved health outcomes) in diabetic patients. Text-message based systems especially, are useful in promoting self-care behaviours as part of a self-management scheme. A deeper understanding of the concept of autonomy is essential to mitigate against the limitations of autonomy in its current state, namely the centrality of rationality. A discussion around alternative terminology and ways to measure improvements may be useful. This can then inform new mHealth designs that generate the best patient outcomes.